2010
DOI: 10.1016/j.biomaterials.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific gene delivery via nanoparticle coating

Abstract: The use of biomaterials for gene delivery can potentially avoid many of the safety concerns with viral gene delivery. However, the efficacy of polymeric gene delivery methods is low, particularly in vivo. One significant concern is that the interior and exterior composition of polymeric gene delivery nanoparticles are often coupled, with a single polymer backbone governing all functions from biophysical properties of the polymer/DNA particle to DNA condensation and release. In this work we develop electrostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 36 publications
1
90
0
Order By: Relevance
“…n Targeting therapy: gene, protein & drug intracellular delivery One of the most attractive concepts in manipulating the fate of stem cells and directing their differentiation into specific cell populations is the use of nanomaterials for intracellular gene delivery (e.g., RNAi and DNA) [91,92]. Generally, viral (e.g., adenoviruses, lentiviruses and retroviruses) and nonviral vectors (e.g., lipids and polymers) can be used for cellular transfection and/or nucleofection, thus offering durable gene expression within stem cells [93][94][95][96].…”
Section: A U T H O R P R O O Fmentioning
confidence: 99%
“…n Targeting therapy: gene, protein & drug intracellular delivery One of the most attractive concepts in manipulating the fate of stem cells and directing their differentiation into specific cell populations is the use of nanomaterials for intracellular gene delivery (e.g., RNAi and DNA) [91,92]. Generally, viral (e.g., adenoviruses, lentiviruses and retroviruses) and nonviral vectors (e.g., lipids and polymers) can be used for cellular transfection and/or nucleofection, thus offering durable gene expression within stem cells [93][94][95][96].…”
Section: A U T H O R P R O O Fmentioning
confidence: 99%
“…Harris and co-workers studied tissue-specific gene delivery via nanoparticle coating (Harris et al, 2010). They prepared cationic nanoparticles with plasmid DNA and then coated their cationic surface with poly anionic poly(glutamic acid)-based peptides with and without cationic insert.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…This importance suggests that the phagocytic activity of bone marrow is a potent target of nanoparticle-based drug delivery. In fact, it has been demonstrated that nanoparticles modified with a specific molecule on their surface are distributed selectively into bone marrow tissues (Harris et al 2010;Mann et al, 2011;Moghimi, 1995;Porter et al, 1992;Schettini et al, 2006;Sou et al 2007Sou et al , 2010Sou et al , 2011a. These bone marrow-specific drug carrier systems are expected to improve diagnostic and therapeutic systems to treat hematopoietic disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AlexaFluor 680 -pDNA 44 . This versatility was also employed to make biotinylated plasmids 43 for in vivo transfection with Lac-PEI.…”
mentioning
confidence: 99%